2021
DOI: 10.1108/jsbed-08-2019-0288
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of being a food artisan entrepreneur: responding to conflicting institutional logics

Abstract: PurposeThe aim of this study is to understand how artisanal food entrepreneurs acting as businesses, which are grounded in the logic of profit and growth, navigate the anti-growth constraints of artisanal logic. The study answers the research question of, how and when do the artisanal entrepreneurs respond to tensions between the small-scale craftsmanship logic and the business growth logic?Design/methodology/approachThis study consists of two cases of artisanal food entrepreneurs situated in rural regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The resilience of artisan business as a hybrid organization can be achieved by the incompatible logics based on the elastic hybridity with which the compatibility between logics can change over time (Gümüsay et al, 2020). Core–Satellite further elaborates and extends the compartmentalization strategy with which hybrid organizations separate logics to follow their demands in different times and places (Battilana & Lee, 2014; Lindbergh & Schwartz, 2021). By exploring a new response, our finding supports the argument made by Norman et al (2004) in a way that organizations will be likely to have better performance when successfully respond to multiple logics in comparison with those that respond to single logic.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resilience of artisan business as a hybrid organization can be achieved by the incompatible logics based on the elastic hybridity with which the compatibility between logics can change over time (Gümüsay et al, 2020). Core–Satellite further elaborates and extends the compartmentalization strategy with which hybrid organizations separate logics to follow their demands in different times and places (Battilana & Lee, 2014; Lindbergh & Schwartz, 2021). By exploring a new response, our finding supports the argument made by Norman et al (2004) in a way that organizations will be likely to have better performance when successfully respond to multiple logics in comparison with those that respond to single logic.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Kraatz and Block (2008, p. 244) define hybrid organizations as “the structural embodiment or incarnation of multiple logics” leading to the fact that “multiple things to multiple people.” When organizations are located in a multiple-logic environment or under pressure from more than one logic, the action at the organizational level and the individual in that organization faces diverse requests and then may be at risk of the consequences resulting from conflicting power and directions of logics (Laihonen & Kokko, 2023; Pache & Thornton, 2020). As stated by Hoyte (2019), artisan business owners “utilize their passion and creativity to make and sell handmade products linked to their cultural heritage because of their openness to newness and openness to innovation.” In front of global mass consumption and changing needs of the market, the artisan business is put on the brink of change for survival and growth (Bislimi, 2022; Lindbergh & Schwartz, 2021). Openness to newness and innovation is one of the critical factors seducing artisan business owners to combine the intangible values of cultural heritage and their creativity with craft production and trading.…”
Section: Logics Counter-institutional Identities and Product Innovationmentioning
confidence: 99%
“…This paper contributes to the academic literature with a bibliometric review of research on entrepreneurship and the food sector at a crucial moment for the world economy, the Covid'19 health crisis, and has several theoretical implications. Firstly, although there are already papers that have studied entrepreneurship in the food sector (Tajvidi and Tajvidi, 2021; Lindbergh and Schwartz, 2021), a bibliometric analysis of publications on both topics had not been carried out. We then contribute by providing knowledge on the research developed by providing information on the evolution of the research, most influential papers and authors, countries and institutions involved, as well as emerging themes that should be taken into account in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the great challenges that the food sector is currently facing and the great opportunities for new projects and companies, it is interesting to know and analyse the scientific production on both structures. Although numerous articles relate the food sector to entrepreneurship (Tajvidi and Tajvidi, 2021;Lindbergh and Schwartz, 2021), no bibliometric articles that analyse the scientific production that relates both terms have been found in the literature. In the field of entrepreneurship, this type of study has been carried out for several years; recently, we found one on international entrepreneurship (IE) (Baier-Fuentes et al, 2019), another on social entrepreneurship (Dionisio, 2019) or even on entrepreneurship education (EE) (Aparicio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the local food movement agenda, entrepreneurial approaches to the re-localization of food production and consumption are widely considered to be community development mechanisms [8,[17][18][19]. Researchers have associated a range of pro-community impacts with local food entrepreneurship that converge to foster economically, environmentally, and socially just, vibrant, and sustainable communities [1,10,20].…”
Section: Literature Reviewmentioning
confidence: 99%